Finding the fit: an examination of strategies used in first- and second-year beginning band instruction to cultivate a sense of belongingness in students - Knopp, Shawn Michael (Kansas State University, 2023)
The purpose of this study was to explore strategies used by Kansas band directors to cultivate a sense of belongingness, through social and emotional learning, in their students during first- and second-year beginning band instruction. The survey sought to reveal the extent to which band directors of first- and second-year beginning band students recognize and understand the principles within belongingness, through social and emotional learning, and if there is intent from these directors to directly address a student’s sense of belongingness through aspects of social and emotional learning. As a means to enhance and encourage awareness of incorporating efficacy and belongingness in their instruction through social and emotional learning, the data highlighted effective practices discovered through the study as it related to developing and fostering belongingness in first- and second-year beginning band students. Kansas band directors of first- and second-year beginning band students who participated in the survey perceive belongingness as when students possess feelings of acceptance, respect, inclusion and support. In their classrooms, belongingness looks like: (a) students who feel safe and free from judgement during rehearsals and performances, (b) students who are not afraid of making mistakes while improving their musicianship, (c) students who recognize their musician peers as caring and supportive and (d) students collaborating in small groups. Participants use a variety of instructional strategies to develop belongingness in their students including: (a) student input, (b) student self-reflection, (c) cooperative learning structures and (d) discussion prompts. Lesser used strategies include: (a) student choice and voice, (b) project-based learning, (c) student self-assessment and (d) culturally responsive instruction.
Keywords: Belongingness; Social and emotional learning; Beginning band; Self-efficacy